Analisis Spasial Penyediaan Fasilitas Pendidikan pada Sekolah Menengah Pertama di Kabupaten Boyolali - Ratih Puspita Dewi (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2016)
The research aimed to know: (1) spatial distribution, distribution pattern and educational facilities reach, (2) the availability of educational facilities, (3) the function of availability of educational facilities at junior high school in Boyolali District. This research used descriptive research method. The population of the research is all junior high school in Boyolali District at 2011, the sampling technique is stratified random sampling. The technique of collecting data are documentation and observation. The technique of data analysis is map analysis and nearest neighbour analysis. The result shown: (1) junior high school spasial distribution mostly located in Boyolali Subdistrict and the least in Selo Subdistrict, the distribution pattern at mountainous topography is random, in the lowland topography also random, and there are 11.1% junior high schools are easy to reach, 81.1% junior high schools are quite easy to reach, and 7.7% junior high schools are difficult to reach; (2) The highest junior high school adequate is in Ampel Subdistrict, Boyolali Subdistrict, Sawit Subdistrict, Banyudono Subdistrict, Sambi Subdistrict, Simo Subdistrict, Karanggede Subdistrict, Klego Subdistrict, Andong Subdistrict, and Wonosegoro Subdistrict, and the least junior high school adequate is in Cepogo Subdistrict; (3) The subdistrict which number of schools are not enough they are: Selo, Cepogo, Musuk, Ngemplak, Nogosari, Kemusu, and Juwangi.